Intestinal Sensing by Gut Microbiota: Targeting Gut Peptides - Covasa, Mihai; Stephens, Richard W.; Toderean, Roxana; Cobuz, Claudiu (Frontiers in Endocrinology, 2019)
Today’s world inhabits more than 2 billion overweight and obese individuals, surpassing, for the first time, the number of people affected by undernutrition.. Obesity and its comorbidities inflict a heavy burden on the global economies and have become a serious threat to individuals’ wellbeing with no immediate cure available. The causes of obesity are manifold, involving several factors including physiological, metabolic, neural, psychosocial, economic, genetics and the environment, among others. Recent advances in genome sequencing and metagenomic profiling have added another dimension to this complexity by implicating the gut microbiota as an important player in energy regulation and the development of obesity. As such, accumulating evidence demonstrate the impact of the gut microbiota on body weight, adiposity, glucose and lipid metabolism and metabolic syndrome. This also includes the role of microbiota as a modulatory signal either directly or through its bioactive metabolites on intestinal lumen by releasing chemosensing factors known to have a major role in controlling food intake and regulating body weight. The importance of gut signalling by microbiota signalling is further highlighted by the presence of taste and nutrient receptors on the intestinal epithelium activated by the microbial degradation products as well as their role in release of peptides hormones controlling appetite and energy homeostasis. This review present evidence on how gut microbiota interacts with intestinal chemosensing and modulates the release and activity of gut peptides, particularly GLP-1 and PYY.